2019
DOI: 10.1093/annonc/mdy526
|View full text |Cite
|
Sign up to set email alerts
|

REVERCE: a randomized phase II study of regorafenib followed by cetuximab versus the reverse sequence for previously treated metastatic colorectal cancer patients

Abstract: 557 (oral presentation in rapid fire abstract session). Translational research results were presented in poster discussion session of the Annual Meeting of the American Society of Clinical Oncology 2018 (1-5 June), and results of quality of life assessment were presented in poster discussion session of the European Society of Medical Oncology World Congress on Gastrointestinal Cancer 2018 (20-23 June). Background: The objective of this randomized phase II trial was to evaluate efficacy and safety of the therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 26 publications
2
44
1
1
Order By: Relevance
“…Patients who had received prior treatment with anti-EGFR antibodies or regorafenib were excluded according to the possible appearance of acquired resistant mutations. [9][10][11] This study was approved by the ethics committees at each institution (National Cancer Center Institutional Review Board, Kansai Rosai Hospital Review Board, Saitama Cancer Center Review Board, Chiba Cancer Center Review Board, National Hospital Organization Shikoku Cancer Center Review Board, Hokkaido University Review Board, Kyushu University Review Board, and Osaka University Review Board), and all patients provided written informed consent. All procedures related to the study were performed in accordance with the Helsinki Declaration.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…Patients who had received prior treatment with anti-EGFR antibodies or regorafenib were excluded according to the possible appearance of acquired resistant mutations. [9][10][11] This study was approved by the ethics committees at each institution (National Cancer Center Institutional Review Board, Kansai Rosai Hospital Review Board, Saitama Cancer Center Review Board, Chiba Cancer Center Review Board, National Hospital Organization Shikoku Cancer Center Review Board, Hokkaido University Review Board, Kyushu University Review Board, and Osaka University Review Board), and all patients provided written informed consent. All procedures related to the study were performed in accordance with the Helsinki Declaration.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…However, effective reintroduction of oxaliplatin and anti-EGFR agents has been limited to patients treated for a duration of 6 months because of discontinuation and reintroduction in these reports. Recently, the REVERCE Study demonstrated that anti-EGFR treatment after regorafenib prolonged the overall survival more than the current standard sequence of treatment with an anti-EGFR agent followed by regorafenib [21]. Furthermore, preclinically, Napolitano et al [22] reported that regorafenib overcame anti-EGFR antibody resistance of colorectal cancer by blocking the mitogen-activated protein kinase (MAPK) and AKT pathways.…”
Section: Discussionmentioning
confidence: 99%
“…An exploratory subgroup analysis suggested that patients who had not received prior targeted therapy (including bevacizumab) had better outcomes with regorafenib than those who had received at least one prior targeted agent [11]. These results, together with more recent evidence [12], suggest that regorafenib treatment prior to targeted therapy may further improve outcomes in patients with mCRC. The current study was designed to investigate the efficacy and safety of regorafenib in patients with antiangiogenic therapynaïve chemotherapy-refractory mCRC.…”
Section: Introductionmentioning
confidence: 86%